Detection of cell surface hydrophobicity, biofilm and fimbirae genes in salmonella isolated from tunisian clinical and poultry meat. - Fethi Ben Abdallah; Rihab Lagha; Khaled Said; Héla Kallel; Jawhar Gharbi (Tehran University of Medical Sciences, 2014)
The aim of this study was to evaluate the ability of 15 serotypes of Salmonella to form biofilm on polystyrene, polyvinyl chloride (PVC) and glass surfaces. .Initially slime production was assessed on CRA agar and hydrophobicity of 20 Salmonella strains isolated from poultry and human and two Salmonella enterica serovar Typhimurium references strains was achieved by microbial adhesion to n-hexadecane. In addition, biofilm formation on polystyrene, PVC and glass surfaces was also investigated by using MTT and XTT colorimetric assay. Further, distribution of Salmonella enterotoxin (stn), Salmonella Enteritidis fimbrial (sef) and plasmid encoded fimbrial (pef) genes among tested strains was achieved by PCR.Salmonella strains developed red and white colonies on CRA and they are considered as hydrophilic with affinity values to n-hexadecane ranged between 0.29% and 29.55%. Quantitative biofilm assays showed that bacteria are able to form biofilm on polystyrene with different degrees and 54.54% of strains produce a strong biofilm on glass. In addition, all the strains form only a moderate (54.54%) and weak (40.91%) biofilm on PVC. PCR detection showed that only S. Enteritidis harbour Sef gene, whereas Pef and stn genes were detected in S. Kentucky, S. Amsterdam, S. Hadar, S. Enteritidis and S. Typhimurium.Salmonella serotypes are able to form biofilm on hydrophobic and hydrophilic industrial surfaces. Biofilm formation of Salmonella on these surfaces has an increased potential to compromise food safety and potentiate public health risk.